2009
DOI: 10.1016/j.acvd.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of exercise training in chronic heart failure

Abstract: Exercise training performed in cardiac rehabilitation centres is an adjuvant therapy in chronic heart failure patients with left ventricular dysfunction; it decreases the deleterious consequences of chronic heart failure. Exercise training attenuates neurohormonal stimulation, the production of proinflammatory cytokines and natriuretic peptide overexpression. Trained patients showed a significant decrease in the peripheral organ injuries encountered in chronic heart failure, with a reduction in vascular resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 56 publications
2
40
1
Order By: Relevance
“…In CHF patients, several studies have suggested that exercise training improves time to clinical worsening and survival [31,32]. In patients with CHF due to coronary artery disease, total mortality was reduced by 27% following exercise training [33].…”
Section: Discussionmentioning
confidence: 99%
“…In CHF patients, several studies have suggested that exercise training improves time to clinical worsening and survival [31,32]. In patients with CHF due to coronary artery disease, total mortality was reduced by 27% following exercise training [33].…”
Section: Discussionmentioning
confidence: 99%
“…Noncompliance with non-pharmacological treatment is related to adverse outcomes 2 and lower quality of life. 3 It is therefore vital to identify those patients who are at risk for noncompliance over a longer period of time, especially since studies have shown that noncompliance is a problem in the HF population. 4 It has been suggested that compliance with a specific recommendation might be a marker for compliance with other recommendations or lifestyle changes.…”
mentioning
confidence: 99%
“…However, the ExT was not initiated simultaneously with CRT, lasted only 3-months and no information on autonomic nervous system (ANS) or potential mechanisms were provided. In recent years, there has been a growing consensus that ExT has beneficial effects in CHF patients [16]. ExT in CHF produce meaningful change in VO 2peak with an expected average improvement of 17% [17].…”
Section: Effects Of Exercise Trainingmentioning
confidence: 99%